Relationship of cataract to radiation sensitivity. Issue 12 (December 1989) - Brown, N A; Shun-Shin, G A; Lewis, P; Cramp, W A; Arlett, C; Cole, J; Waugh, A P; Stephens, G
Abstract : Considerable exposure to radiation always causes posterior subcapsular cataract (PSC). This investigation was conducted to ascertain whether cellular hypersensitivity to radiation may be identified as a possible cause of cataract in persons exposed to low levels of radiation. Patients were studied in whom PSC had followed probable exposure to low levels of radiation or in whom PSC had developed before the age of 60 without known exposure. The patients with cataract were compared with age and sex matched controls without cataract. Radiation sensitivity was estimated by measuring clonal growth of skin fibroblasts and peripheral blood lymphocytes after exposure to graded doses of radiation and by measuring postirradiation reconstruction of separated nuclear material from lymphocytes. The results show variations in the level of radiation sensitivity between the patients, without significant differences from the controls. It is concluded that radiation hypersensitivity, as tested by the methods used in this study, is not normally associated with the development of posterior subcapsular cataract.